Removal of External Deposits on Boiler Tubes - De, C. P.; Chaudhuri, J. C.; Buch, K. P.; Audi, A. K. (Defence Science Journal, 2014)
The superheater tubes in Port and Starboard boilers were found to have completely clogged by heavy deposits, which on analysis mainly vanadium pentoxide and sodium sulphmatter. The cleaning of the deposits was accomplished by alternate spraying with 15-20 per cent hydrogen peroxide and washing with hot water jets. Over the past two years, since the date of cleaning, the IN ship is operating without any trouble in the boilers.